Pancasila as a Paradigm in Inter-Religious Life in Indonesia - Gusman; Amelia; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
The focus of the study in this article is about Pancasila as a paradigm in inter-religious life. This paper moves from the social phenomena of post-reform statehood which still cause horizontal conflict in the community. Exalting this conflict uses religion as its basis. From the study in this paper, it can be seen that the basic values and philosophies contained in Pancasila actually already contain the paradigm of humane thinking. The content contained in the principles and teaching values of Pancasila requires that citizens always live in harmony and respect each other among religious adherents, so that Indonesian people will be able to realize even though different religions and beliefs, but united in unity and unity as enshrined in the principle of unity Indonesia, in order to achieve the glory of the nation and state. From this study it can also be seen that a deeper study is needed to embody the values of Pancasila as a paradigm of harmony.